Macroeconomic Uncertainty and Empirical Research Results of its Quantitative Measurement in Georgia - Kbiladze, David; Metreveli, Shorena; Kbiladze, Tamar (Ekonomika, 2021)
The present article describes the approaches and definition of the concept of uncertainty proposed by its authors, a quantitative evaluation of uncertainty, and materials of the empirical study used to explore the said issues on the example of macroeconomics of Georgia. We hope that the views given in the article will be useful for developing countries, particularly for the economic policy-makers in the post-communist states, as well as for the academic and scientific circles engaged in the studies of the above-listed issues.